2007
DOI: 10.1002/bip.20712
|View full text |Cite
|
Sign up to set email alerts
|

The energetics of i‐DNA tetraplex structures formed intermolecularly by d(TC5) and intramolecularly by d[(C5T3)3C5]

Abstract: Cytosine-rich DNA at low pH adopts an antiparallel tetraplex structure via the intercalation of two partially protonated, parallel stranded duplexes. This intriguing structural motif has been named i-DNA. We have used a combination of spectroscopic and calorimetric techniques to characterize the properties of an intermolecular i-DNA formed by d(TC(5)) and an intramolecular i-DNA formed by d[(C(5)T(3))(3)C(5)]. Our measurements reveal that both i-DNA complexes are enthalpically stabilized by 6.5-7.0 kcal/mol(ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 86 publications
5
43
0
Order By: Relevance
“…In addition, all of oligonucleotides showed an obvious and unaltered turning point in absorbance versus temperature curve of 265nm ( Figure S2d, Supporting Information) and a solid UV melting temperature (Table1). This further supported the formation of intercalated i-motifs [45].…”
Section: Formation Of the Interstrand I-motif In Solutionsupporting
confidence: 66%
See 2 more Smart Citations
“…In addition, all of oligonucleotides showed an obvious and unaltered turning point in absorbance versus temperature curve of 265nm ( Figure S2d, Supporting Information) and a solid UV melting temperature (Table1). This further supported the formation of intercalated i-motifs [45].…”
Section: Formation Of the Interstrand I-motif In Solutionsupporting
confidence: 66%
“…All measurements were performed at least three times; the T m values differed by less than 0.5°C [44]. It should be noted that the melting profiles of interstrand i-motifs mainly reflect the stability of fully intercalated i-DNA tetraplex structures, when the strands were equilibrated with sufficient time [45]. This is why the turning point of melting curves can be considered to be the T m of such structures.…”
Section: Uv Absorption Spectrophotometrymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, structural NMR studies have shown that cytosine-rich DNAs form an unusual quadruplex structure ("i-motif DNA") consisting of two intercalated duplexes made up of hemiprotonated base pairs [27,28]. This structure, which may be biologically significant [29][30][31], is formed when two parallel-stranded duplexes associate in head-to-tail fashion, forming intercalated hemiprotonated base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the familiar duplex structure, nucleic acids can form a variety of non-canonical triplex (4,5), quadruplex (6) or i-motif (3,7,8) structures. Some of these structures have been detected in living cells (9)(10)(11) where they may play key roles in a variety of biological processes, including replication, transcription, oncogene expression, and telomere functions (11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%